2015
DOI: 10.1038/eye.2015.62
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of hinokitiol on human corneal epithelial cells: an in vitro study

Abstract: Purpose This study assessed the antiinflammatory effect and mechanism of action of hinokitiol in human corneal epithelial (HCE) cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Moreover, poly (I:C) could be directly bound by the extracellular domain of CD14, thereby facilitating poly (I:C) uptake and enhancing TLR3 activation [10]. Poly (I:C) triggered TLR3 activation, followed by downstream inflammatory cascades have been reported in many corneal pathologies [1113]. Recently, emerging evidences showed that TLR3 could also trigger the generation of reactive oxygen species (ROS), an essential secondary messenger that was required for NF-κB activation, leading to innate immune response [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, poly (I:C) could be directly bound by the extracellular domain of CD14, thereby facilitating poly (I:C) uptake and enhancing TLR3 activation [10]. Poly (I:C) triggered TLR3 activation, followed by downstream inflammatory cascades have been reported in many corneal pathologies [1113]. Recently, emerging evidences showed that TLR3 could also trigger the generation of reactive oxygen species (ROS), an essential secondary messenger that was required for NF-κB activation, leading to innate immune response [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although antibacterial treatment is an important approach against pneumonia, regulating excessive inflammation is equally essential [ 52 , 53 ]. Hinokitiol was previously shown to reduce the transcription of inflammatory cytokines from epithelial cells in vitro [ 6 , 54 ]. In this study, intratracheal administration of hinokitiol decreased the concentrations of cytokines and chemokines in BALF and serum.…”
Section: Discussionmentioning
confidence: 99%
“…Hinokitiol (β-thujaplicin) is a naturally occurring monoterpenoid found in the wooden part of trees in the Cupressaceae family. It is a tropolone derivative and is widely used in oral care and therapeutic products for its potent, broad-spectrum antiviral, antimicrobial [4] , antifungal, anti-inflammatory [5] , [6] , and anticancer properties [7] . Additionally, it has been approved as a food additive and does not accumulate in the body.…”
Section: Background To Hypothesismentioning
confidence: 99%